A risk management methodology for protozoa control in drinking water supply systems - Duarte, António A. L. Sampaio (2012)
Over the last two decades, enteric protozoa have been recognized as a major concern regarding waterborne diseases, mostly due to the occurrence of a high number of outbreaks worldwide, leading to serious public health problems. The complexity of these problems advises an integrated analysis of the microorganisms’ characteristics and life cycle linked with the catchment-to-consumer drinking water system in order to bring light upon the failures that underlie these undesirable events. Several studies have been developed in order to mitigate these impacts on public health, attending to the main paths of water contamination, and the processes of advanced treatment and monitoring. Moreover, risk management methodologies were also improved in order to provide the incorporation of the multiple barrier approach in drinking water risk assessment tools, which must be able to identify hazards and the major vulnerabilities of drinking water contamination by pathogenic protozoa. In this work, the authors present a protozoa control strategy, based on a risk management methodology and consisting of three fundamental steps: identification of hazardous events and drinking water system failures; qualitative risk assessment associated with the identified events and failures; definition of risk mitigation measures for protozoa control. A case study will be used for testing the proposed methodology towards the design of a strategic plan to minimize the resilience of the events related to the presence of these pathogens in water sources and to increase the sustainability of water resource management.